(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The article describes the use of methodological methods in the teaching of artistic subjects, the teaching methods, the activities of the teacher and the learner in the educational process, how to organize and conduct the educational process, and in this process, what actions the learners should perform